(3GdahGFO GdYdjI aj GdeSGFd GdTQYjI GdLdjIs - (3GdfKGQj, eMeO Hf Ydj, cGf MjG (B1112 (3g`s ((3eMeO Hf Ydj GdeaJj (B( (3GdeDda (B)s)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdYdj GdYdGe hHYO agPg aQGFO ahGFO CaGOfG GdCSJGP HgGA GdESdGe Ydi GdfKGQj GdeaJj HbjUQjI hSejJgG HGdahGFO GdYdjI aj GdeSGFd GdTQYjI GdLdjIs
(3BNQgG (B:s
(3jTgO ef GdETgGO dG ef GdTgGOI hbhdfG GdaQY efUhH Ydi GdeaYhdjI dG eQahY Ydi GdaGYdjI MJi jchf HjfgeG JfGbV aMeOG MeOG Ke MeOGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 550s
(3EjVGM Gdecfhf (B2 / 208s
(3gOjI GdYGQajf (B2 / 208s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs